(untitled) (BIS Humanities and Social Science, 2026)
The development of digital communication technology has encouraged governments to adapt in disseminating information and building effective relationships with the public. Social media, particularly Instagram, has become a strategic platform in Digital Public Relations practices to construct a responsive, open, and participatory government image. The Yogyakarta City Government, through its official account @pemkotjogja, actively utilizes social media to establish interactive and transparent communication with the public. The growing use of social media among citizens presents challenges for the government in managing information, maintaining content consistency, and fostering active public engagement. This study examines how the Yogyakarta City Government implements its Digital Public Relations strategy through Instagram in building a responsive government image. The research employs a qualitative descriptive method, with data collected through in-depth interviews involving the public relations staff, @pemkotjogja’s content management team, and two active followers of the account, complemented by observation and documentation of uploaded content. Data validity was tested using triangulation of techniques and sources, while analysis followed Miles and Huberman’s interactive model through data reduction, presentation, and conclusion drawing. The results show that the Yogyakarta City Government applies a multi-platform, collaborative, and technology-adaptive strategy. Instagram serves as the main medium for disseminating information, facilitating two-way interaction, and strengthening a transparent and responsive government image. Quick responses to public inquiries, a human-centered communication style, and consistent information delivery have proven effective in building trust and closeness between the government and the public.